Nanostructured Soft Matter with Magnetic Nanoparticles. (10th March 2016) - Tokarev, Alexander; Yatvin, Jeremy; Trotsenko, Oleksandr; Locklin, Jason; Minko, Sergiy
Abstract : Magnetic field imaging in living specimens with magnetic nanoparticles as contrasting agents has attracted significant interest in the rapidly developing field of nanomedicine. Developments in this field have also stimulated research into the synthesis and design of functionalized magnetic nanoparticles that find applications in broader areas of materials science beyond contrasting for biomedical applications. This article provides a brief discussion of the methods for synthesis and surveys the surface functionalization chemistry of magnetic nanoparticles, along with various approaches for magnetic nanoparticle manipulation and assembly in uniform and nonuniform magnetic fields. Abstract : The methods for the synthesis of magnetic nanoparticles of different shapes and sizes are briefly discussed. Additionally, their surface functionalization chemistry is surveyed, along with various approaches for magnetic nanoparticles manipulation and assembly in uniform and nonuniform magnetic fields to deliver, generate, and degrade structures on both microscopic and macroscopic scales.